MINAT BELAJAR SISWA DALAM PEMBELAJARAN KEAGAMAAN DI MADRASAH DINIYAH ISLAMIYAH PATEGUHAN GONDANGWETAN PASURUAN - Mubailah, Amiroh; Yusuf, Achmad (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2021)
A person's interest in teaching and learning is very important to achieve a learning goal. Without interest, a person will not be able to do something wholeheartedly. Especially in religious learning in Madrasah diniyah, which is a sensitive matter concerning religious matters. So, there is a need for knowledge about a student's interest in religious learning in Madrasah Diniyah Islamiyah in order to achieve the learning objectives well. This research uses qualitative approach with case study type. The data in this study there are two include primary data, and secondary data. The results showed that a person's interest in religious learning at Madrasah Diniyah Islamiyah can be seen from (a) the increase in the number of students who enter each year, and (b) the enthusiasm of students in undergoing learning at Madrasah Diniyah. The inhibiting factors for this student personality formation process can be in the form of (a) parents' lack of awareness of religion and (b) the existence of a full day school. While the supporting factors for the process of forming student personality are (a) changes in the public's perception of the urgency of religious education (b) the emergence of millennial figures who uphold religious attitudes derived from religious learning (c) the existence of the Pasuruan Perbub No. 21 of 2016 concerning Mandatory Madrasah Learning Diniyah (d) socializing with friends